Exploring the potential of TEM analysis for understanding cooking at prehistoric feasting sites - Katie E. Faillace (Nature Portfolio, 2020)
Abstract This study explores the utility of transmission electron microscopy (TEM) analysis of bone collagen for investigating prehistoric cooking. Approaches to cooking practices have relied principally on artefactual evidence, macroscopic bone modification, and organic residue analysis. However, direct evidence for cooking of bone has been limited. Richter and Koon successfully applied TEM analysis of collagen to determine heating to modern and medieval bones, but this method has yet to be experimentally tested using prehistoric remains. Collagen will denature at relatively low temperatures, such as during roasting, boiling, or baking. The denaturation of collagen causes predictable structural changes that can be viewed through TEM. Zooarchaeological remains of sheep and pig with minimal taphonomic modifications were analysed from four later prehistoric (c. 800–500BC) sites in Britain (n = 33). Humeri and phalanges were selected to compare elements with high and low meat yields. Samples were classified into ‘Heated’ and ‘Unheated’ groups consistent with previous studies, and variable patterns were observed between different sites and taxa. Analytical limitations have hindered the study of cooking in the past, but this study demonstrates the potential of this taphonomic method for exploring prehistoric cooking practices and provides a springboard for wider studies.